Potential Utilization of Modified Multitarget CAR-T Cells as an Advanced Immunotherapy for Glioblastoma: A Systematic Review - Elysia Gita Pascadea; Diondra Eka Rizkiawan (Departemen Neurologi Fakultas Kedokteran Universitas Indonesia, 2025)
Introduction: Glioblastoma (GBM) is the most common and aggressive malignant brain tumor, characterized by high morbidity and mortality. Standard treatments—surgery, radiotherapy, and chemotherapy—are often ineffective due to tumor heterogeneity and recurrence. Immunotherapy, particularly chimeric antigen receptor T (CAR-T) cell therapy, has emerged as a promising alternative. This systematic review evaluates the potential of modified multitarget CAR-T cells in addressing GBM’s challenges. Material and methods: A systematic review was conducted following PRISMA 2020 guidelines. Searches in PubMed, ScienceDirect®, ProQuest, EBSCOhost®, SAGE®, ClinicalKey®, and Scopus focused on studies from the past decade. Data were analyzed to assess the efficacy, safety, and feasibility of multitarget CAR-T therapies. Of 1,512 identified studies, 11 met the inclusion criteria. Findings indicate multitarget CAR-T cells enhance tumor recognition and immune activation, reducing immune evasion. CAR-T designs targeting EGFRvIII, IL13Rα2, HER2, and GD2 exhibited improved cytotoxicity, eradicated tumors, demonstrated long-term memory response, and were able to achieved complete tumor clearance. Studies found that CAR-T cells therapy in GBM enhanced tumor suppression and prolonged survival in glioblastoma patients. Discussion: Originally developed for hematologic malignancies, CAR-T therapy is expanding to GBM by targeting tumor-associated antigens (TAAs) like CEA, GPC-3, MUC1, VEGFR2, EGFRvIII, IL13Rα2, HER2, and GD2. However, challenges such as the immunosuppressive tumor microenvironment (TME), antigen loss, and limited tumor penetration hinder efficacy. Strategies like multitarget CAR-T cells, immune checkpoint inhibition, and localized delivery methods may improve outcomes. Conclusion: CAR-T therapy holds potential for GBM treatment, but further research is required to enhance its effectiveness and clinical applicability.